2014
DOI: 10.1111/crj.12217
|View full text |Cite
|
Sign up to set email alerts
|

Delays for diagnosis and treatment of lung cancers: a systematic review

Abstract: Background and Aims:The impact of diagnosis and treatment delays for non-small cell lung cancer management is poorly understood, even if the literature on the subject is currently increasing in importance. We have few indicators that can serve as reference for quality assurance actions. The objective of this review was to review the literature on the subject. Methods: A literature search, using the words 'human lung cancer delay' and 'human lung cancer waiting time' , was undertaken in Medline database. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 19 publications
4
49
1
Order By: Relevance
“…In our study, 57% of patients had locally advanced or metastatic disease at presentation. Long management delays are most frequently found in less-symptomatic patients, and hence potentially carry a better prognosis; in contrast, patients with more advanced disease often have more severe symptoms that require expedited investigation and earlier initiation of treatment 23 . Time to treatment might become a more important factor for patients with more rapidly growing tumours or with longer survival times.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 57% of patients had locally advanced or metastatic disease at presentation. Long management delays are most frequently found in less-symptomatic patients, and hence potentially carry a better prognosis; in contrast, patients with more advanced disease often have more severe symptoms that require expedited investigation and earlier initiation of treatment 23 . Time to treatment might become a more important factor for patients with more rapidly growing tumours or with longer survival times.…”
Section: Discussionmentioning
confidence: 99%
“…This result is more than acceptable according to current recommendations. A review including 65 papers published between 2007 and 2016 measuring the timeliness of LC diagnosis and treatment in 21 countries found that the most commonly reported wait‐time intervals were from diagnosis to treatment, first visit with a specialist to a confirmed diagnosis, and symptom onset to the first physician visit . This systematic review reported a median delay of 14 days between the first symptom and the first consultation with a general practitioner, 24 days before consulting a specialist, and a range of 29 to 73 days before treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies that assessed the delay to an LC diagnosis showed median diagnostic intervals between the first symptomatic presentation and diagnosis of LC of approximately 180 days, and in some cases exceeding 300 days . In a systematic review, the median delays to therapeutic care after symptom appearance varied from 47 to 138 days . Some studies have focused on the differences in ambulatory versus hospitalized management of LC, others on tumor size or comorbidities, with different results .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that treatment delays are prognostic in lung cancer [26, 27]. We therefore recommend collecting the time from diagnosis of lung cancer to initiation of treatment.…”
Section: Resultsmentioning
confidence: 99%